2009
DOI: 10.1089/pho.2008.2302
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on the Influence of Nd:YAG Laser Irradiation on Microleakage Associated with Two Filling Techniques

Abstract: Objective: This study investigates the effects of Nd:YAG laser irradiation on apical and coronal seals, when used prior to two root canal filling techniques. Background Data: Limited information exists regarding the effects of morphologic changes to dentin walls following Nd:YAG laser irradiation on the sealing ability of root fillings. Methods: Two hundred forty teeth were analyzed by observing coronal and apical leakage of Indian ink (DL), and 60 were analyzed for through-and-through leakage using the fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…He et al, 45 investigating the temperature at the outer surface of a root after Nd:YAG lasing at different power settings, clearly demonstrated and confirmed what others 13,16,44 had already pointed out: thermal and morphologic changes seen at the apical third of the roots were greater than those in the coronal third, suggesting that caution should be used when irradiating the apical part of the root, to prevent periodontal injury. They demonstrated that root dentin thickness, especially in the apical third, was an important parameter in the conductance of energy and hence temperature toward the periodontal ligament.…”
Section: Nd:yag and Microleakage S-47supporting
confidence: 57%
See 4 more Smart Citations
“…He et al, 45 investigating the temperature at the outer surface of a root after Nd:YAG lasing at different power settings, clearly demonstrated and confirmed what others 13,16,44 had already pointed out: thermal and morphologic changes seen at the apical third of the roots were greater than those in the coronal third, suggesting that caution should be used when irradiating the apical part of the root, to prevent periodontal injury. They demonstrated that root dentin thickness, especially in the apical third, was an important parameter in the conductance of energy and hence temperature toward the periodontal ligament.…”
Section: Nd:yag and Microleakage S-47supporting
confidence: 57%
“…13,16 So the impact of morphologic changes of the rootcanal wall due to the Nd:YAG on the lateral seal of a root filling could be investigated.…”
Section: S-46mentioning
confidence: 99%
See 3 more Smart Citations